2020
DOI: 10.3233/thc-191752
|View full text |Cite
|
Sign up to set email alerts
|

A computer-aided method based on geometrical texture features for a precocious detection of fetal Hydrocephalus in ultrasound images

Abstract: BACKGROUD: Hydrocephalus is the most common anomaly of the fetal head characterized by an excessive accumulation of fluid in the brain processing. The diagnostic process of fetal heads using traditional evaluation techniques are generally time consuming and error prone. Usually, fetal head size is computed using an ultrasound (US) image around 20–22 weeks, which is the gestational age (GA). Biometrical measurements are extracted and compared with ground truth charts to identify normal or abnormal growth. METHO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Several classification methods can be employed for pattern recognition. Nevertheless, for multiple categorization works [32,33], it has been confirmed that DNN presents a highquality tool. To acquire authentic classification results, we have selected the PG region of different images for assembling the training dataset of the network.…”
Section: Classification Of Pg Lesion Using Dbn-dnn Classifiermentioning
confidence: 99%
“…Several classification methods can be employed for pattern recognition. Nevertheless, for multiple categorization works [32,33], it has been confirmed that DNN presents a highquality tool. To acquire authentic classification results, we have selected the PG region of different images for assembling the training dataset of the network.…”
Section: Classification Of Pg Lesion Using Dbn-dnn Classifiermentioning
confidence: 99%
“…Numerous classifiers can be used for pattern acknowledgement. It has been substantiated that the neural network method is an efficient tool for different classification works [25]. We have selected the most discriminative characteristics to prepare the training dataset of the network.…”
Section: Classification Proceduresmentioning
confidence: 99%
“…PCA consists in finding a subspace allowing us to classify the new components in order of decreasing importance in order to reduce the dimension of the original space. The transition matrix of the new space is obtained by maximizing the variance between the original variables [25,26]:…”
Section: Classification Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…To secure a reasonable judgment amid the three tested neural network methods, the same network structure was trained for each one in different experiments based on suitable features. The projected ConvNet depends on advanced algorithms for specifying the best network structure [33]. In this context, the cross-validation procedure was employed to choose the relevant ConvNet structure in the training and test phases of ECG signal datasets [24].…”
Section: 𝐴𝐶 = 𝑇𝑃 + 𝑇𝑁 𝑇𝑃 + 𝐹𝑁 + 𝑇𝑁 + 𝐹𝑃mentioning
confidence: 99%